О значении проповеди Церкви в жизни ранневизантийского полиса на примере деятельности Иоанна Златоуста - Горайко, А. В. (Давнина. Харківський історико-археологічний щорічник, 2016)
SammuryA. Gorayko. On the Meaning of the Church’s Sermon in the Life of the Early-Byzantine Polis Exemplified by Activities of John ChrysostomDuring time of John Chrysostom (341/7–407) as a preacher of the Antiochian and Constantinople churches, ecclesial sermon became a noticeable event within the urban life of the Early-Byzantine Empire. Eloquence on the pulpit was not just natural but also essential for a preacher providing Chrysostom with growth of his talent and influence. All his efforts were directed at the elevating morality of the contemporary society. Church, in his thought, was to be common Christian school. None of the Church fathers has spoken that largely on social themes as John Chrysostom. The Church’s activity had a positive impact on the course of public life in a city, although it would take years for qualitative changes into situation of social relations of polis, but the actions from Chrysostom’s enemies hindered to solving this problem.